Investigation on the co-combustion of oil shale and municipal solid waste by using thermogravimetric analysis. (1st June 2016) - Fan, Yunlong; Yu, Zhaosheng; Fang, Shiwen; Lin, Yan; Lin, Yousheng; Liao, Yanfen; Ma, Xiaoqian
Highlights: Co-combustion of oil shale with municipal solid waste created significant changes. Blending with municipal solid wastes could improve the combustion performance. 10–30% of oil shale in the blends could be determined as the optimum ratio range. Activation energy were calculated by the conversion rate and different proportion. Abstract: The aim of this study is trying to reveal the thermal characteristics and kinetics of oil shale, municipal solid waste and their blends in the combustion process which are needed for efficient utilization. The combustion experiment is carried out in a thermogravimetric simultaneous thermal analyzer, where the temperature ranged from 110 °C to 900 °C at three different heating rates as 10 °C/min, 20 °C/min and 30 °C/min. Their kinetics were studied by Ozawa–Flynn–Wall and Friedmen methods. According to the data analysis, combustion characteristic index increased progressively with the increase of the proportion of municipal solid waste. And it's suggested that there was certain interaction in the combustion process of oil shale and municipal solid waste. The average activation energy of the blends reached the minimum value, 177.7927 kJ/mol by Ozawa–Flynn–Wall method and 167.4234 kJ/mol by Friedmen method, when the proportion of MSW was 70%.